Charge Cluster-to-Alanine Scanning of UL128 for Fine Tuning of the Endothelial Cell Tropism of Human Cytomegalovirus - Schuessler, Andrea (American Society for Microbiology (ASM), 2008)
The viral genes UL128, UL130, and UL131A have been identified as major determinants of endothelial cell (EC) tropism of human cytomegalovirus (HCMV), with deletion of either gene causing a null phenotype. We hypothesized that a functional scanning of these genes by minor genetic modifications would allow for the generation of mutants with an intermediate phenotype. By combining charge cluster-to-alanine (CCTA) mutagenesis with markerless mutagenesis of a bacterial artificial chromosome-cloned endotheliotropic HCMV strain, we analyzed UL128 in order to identify functional sites and hence enable targeted modulation of the EC tropism of HCMV. A total of nine mutations in eight charge clusters were tested. Three of the CCTA mutations severely reduced EC tropism, three were irrelevant, two had a weak effect on cell tropism, and one mutation in the most C-terminal cluster caused an intermediate phenotype. All of the highly effective mutations were located in a core region (amino acids 72 to 106) which appears to be particularly crucial for EC tropism. The intermediate effect of mutations in the C-terminal cluster could be modulated by varying the number of amino acids replaced with alanine. This study provides a rational approach for targeted modulation of HCMV cell tropism, which may aid in the development of HCMV strains with a desired degree of attenuation.